THE ROLE OF WALL NEWSPAPERS IN THE CONSTRUCTION OF SOCIALISM IN TURKESTAN - Nilufar Namazova (Modern American Journals, 2025)
When the Bolsheviks came to power in Turkestan at the end of 1917, a decree was issued to close all bourgeois newspapers. The issue of organizing a Soviet press with new content and essence was put on the agenda. In Turkestan, the press was also supposed to become the most important tool for building socialism. However, there were a number of obstacles to using the press as a means of propaganda to mobilize the people in support of the new "populist" government. Firstly, when the Bolsheviks came to power, there were no other "forces" working in the newspapers in Turkestan, so it was necessary to attract modern journalists to work in the press. They had previous experience, but until then they had not supported the ideas of the Bolsheviks. Secondly, the part of the population reading newspapers was a minority. On Lenin's instructions, the issue of increasing the number of print workers at the expense of the worker-peasant masses was put on the agenda, “by completely removing the rotten intelligentsia... harmful” [1], which required the training of new personnel. In this case, the first to be involved in newspaper work were employees of sects and state institutions. In 1920, at the first meeting of press workers, an order was given to create literary colleges at parties, trade unions and other organizations, and to oblige workers of councils and sects to work regularly as newspaper correspondents.